2020
DOI: 10.1039/d0bm00962h
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymers-calcium phosphate antibacterial coating reduces the pathogenicity of internalized bacteria by mesenchymal stromal cells

Abstract: A multifunctional material system that kills bacteria and drives bone healing is urgently sought to improve bone prosthesis. Herein, the osteoinductive coating made of calcium phosphate/chitosan/hyaluronic acid, named Hybrid, was...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
(80 reference statements)
0
12
0
Order By: Relevance
“…PLA-d and PLA 90 /HA 10 -d scaffolds were placed in 24-well plates treated for low cell binding surface (Nunclon Sphera Surface, Thermo Scientific) for the cell proliferation study. Mesenchymal stromal cells from dental pulp (MSCs) of 8 independent donors were isolated [42] and amplified at a density of 3 × 10 3 cell/cm 2 in α-MEM (Lonza) supplemented with 10% heat-inactivated (56 • C, 30 min) fetal bovine serum (FBS), 1% penicillin/streptomycin/amphotericin B (PSA), and 1% glutamax (v/v, Gibco) and maintained in a humidified atmosphere of 5% CO 2 at 37 • C with a medium change every two days. MSCs were seeded at a density of 2 × 10 4 cells per scaffold and were cultured for 21 days.…”
Section: Biological Studiesmentioning
confidence: 99%
“…PLA-d and PLA 90 /HA 10 -d scaffolds were placed in 24-well plates treated for low cell binding surface (Nunclon Sphera Surface, Thermo Scientific) for the cell proliferation study. Mesenchymal stromal cells from dental pulp (MSCs) of 8 independent donors were isolated [42] and amplified at a density of 3 × 10 3 cell/cm 2 in α-MEM (Lonza) supplemented with 10% heat-inactivated (56 • C, 30 min) fetal bovine serum (FBS), 1% penicillin/streptomycin/amphotericin B (PSA), and 1% glutamax (v/v, Gibco) and maintained in a humidified atmosphere of 5% CO 2 at 37 • C with a medium change every two days. MSCs were seeded at a density of 2 × 10 4 cells per scaffold and were cultured for 21 days.…”
Section: Biological Studiesmentioning
confidence: 99%
“…This multilayer film possessed a contact-killing effect reducing ~90% the viability of Gram-positive S. aureus and Gram-negative Pseudomonas aeruginosa ( P. aeruginosa ) strains after 48 h contact. Moreover, Wharton’s jelly (WJ-SCs), dental pulp (DPSCs), and bone marrow (BM–MSCs)-derived stromal cells were not only able to produce immunomodulatory mediators but also release antibacterial and antibiofilm agents effective against S. aureus and P. aeruginosa strains [ 100 ]. In the same line, HA was also alternatively deposited with polyarginine (PAR) leading to antimicrobial multilayer films.…”
Section: Overview Of the Performance Of Natural Lbl Films In Selected Biomedical Applicationsmentioning
confidence: 99%
“…By using simultaneous spray coating of interacting species process, bone-side collagenic membrane (Bio-Gide ® ; an FDA-approved and commonly applied as a collagen membrane in a broad range of clinical settings) was sprayed with calcium saturated solution supplemented with chitosan (CHI) and phosphate saturated solution supplemented with hyaluronic acid (HA), in the same conditions as previously published (i.e., 50 simultaneous spray cycles for 2 s) [ 17 ]. The choice of CHI (polycation) and HA (polyanion) as polyelectrolyte complexes was motivated by their intrinsic antibacterial properties against Gram-positive and Gram-negative bacteria strains [ 16 ]. Chitosan/hyaluronic coating showing an unsuccessful build-up and instability in physiological media was rejected as a control.…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan (CHI) and hyaluronic acid (HA) are largely investigated in bone regenerative medicine as CHI forms polycation-polyanion complexes in the presence of HA and its amino groups make it specifically relevant for the biomineralization process. We recently indicated that it is possible to endow CaPs with osteoinductive properties by optimizing the material characteristics and by adding CHI and HA during the nucleation [ 14 , 15 , 16 ]. The objective of this study was to functionalize the bone-side of the collagenic membrane, currently used in the GBR procedure, with CaP, CHI and HA components.…”
Section: Introductionmentioning
confidence: 99%